Effect of different activation protocol on generation of parthenogenetic embryos in caprine - PANKAJ, R S; SATISHA, K B; VENKATESH, V; GUPTA, R; KUMAR, K; DAS, B C; MAJUMDAR, A C; BAG, S; RANJAN, R (The Indian Journal of Animal Sciences, 2012)
The present study was carried out to compare the different activation protocol for generation of parthenogenetic embryos in caprine. For parthenogenetic embryo production, 6 activation protocols, viz. 7% ethanol in modified synthetic oviductal fluid (mSOF) for 5 min (P-1), 5µM ionomycin in mSOF for 5 min (P-II), 27 h maturation in maturation media containing 10 and 20 µg/ml cytochalacin B (CCB) followed by activation with (a) 7% ethanol in mSOF for 5 min (P-III, P-IV), or (b) 5µM ionomycin in mSOF for 5 min (P-V and P-VI). All these treatments were followed by 4 h incubation with 2mM 6-dimethylaminopurine (6-DMAP) in mSOF. The activated oocytes were further cultured in mSOF for embryo development. The cleavage rate was higher when oocytes were activated by ionomycin than ethanol but further embryo development was better in ethanol activated oocytes. When oocytes were matured in presence of CCB followed by ionomycin or ethanol activation, the cleavage rate and embryo development did not change significantly and was almost similar to when oocytes were activated simply by ethanol or ionomycin. The study indicated that ethanol and ionomycin alone or even in combination with cytochalacin B induced activation and parthenogenetic development of in vitro matured caprine oocytes.